Conversion therapy for unresectable intrahepatic cholangiocarcinoma using gemcitabine plus S-1 combined with PD-1 inhibitors: a case report - Zhao, Shuangying; Zhang, Xiaodong; Luo, Jialiang; Yan, Huanjun; Zhang, Jianlei; Lin, Rongfeng; Zhu, Kelei (Frontiers in Oncology, 2025)
Intrahepatic cholangiocarcinoma (iCCA) is a highly malignant tumor of the liver and gallbladder, which is usually diagnosed at an advanced stage and the opportunity for surgery is lost. Therefore, conversion therapy is important to convert the iCCA into a resectable state. In recent years, the conversion protocol of immuno-chemotherapy has been applied for advanced liver cancer. However, little has been reported about iCCA conversion therapy. The aim of this report is to present the results of conversion therapy with Gemcitabine plus S-1 (GS) combined with PD-1 inhibitors (Zimberelimab) in a 74-year-old female IIIB iCCA patient. After 6 cycles of conversion therapy, enhanced CT showed that the patient’s tumor had shrunk to nearly half its original size, making radical resection possible. Postoperative pathology showed a complete pathological response. This provides a new way to convert advanced iCCA into resectable state.